Long-Term Outcomes of Surgical Aortic Valve Replacement in Patients with Rheumatoid Arthritis - Malmberg Markus; Palomäki Antti; Sipilä Jussi O. T.; Rautava Päivi; Gunn Jarmo; Kytö Ville (MDPI, 2022)
Background: Patients with rheumatoid arthritis (RA) have increased risk of developing cardiovascular disease and events. Little is, however, known about the influence of RA to the outcomes after surgical aortic valve replacement (SAVR). Methods: In a retrospective, nationwide, multicenter cohort study, RA patients (n = 109) were compared to patients without RA (n = 1090) treated with isolated SAVR for aortic valve stenosis. Propensity score-matching adjustment for baseline features was used to study the outcome differences in a median follow-up of 5.6 years. Results: Patients with RA had higher all-cause mortality (HR 1.76; CI 1.21-2.57; p = 0.003), higher incidence of major adverse cardiovascular events (HR 1.63; CI 1.06-2.49; p = 0.025), and they needed more often coronary artery revascularization for coronary artery disease (HR 3.96; CI 1.21-12.90; p = 0.027) in long-term follow-up after SAVR. As well, cardiovascular mortality rate was higher in patients with RA (35.7% vs. 23.4%, p = 0.023). There was no difference in 30-day mortality (2.8% vs. 1.8%, p = 0.518) or in the need for aortic valve reoperations (3.7% vs. 4.0%, p = 0.532). Conclusions: Patients with rheumatoid arthritis had impaired long-term results and increased cardiovascular mortality after SAVR for aortic valve stenosis. Special attention is needed to improve outcomes of aortic valve stenosis patients with RA after SAVR.